Development of E-Supplements of Biomordan from Cengkodok (Melastoma malabathricum) Leaves For Learning Green Chemistry - Khofifah Aditha Parawansa; Masriani Masriani; Risya Sasri; Ajuk Sapar; Erlina Erlina (Jurnal Inovasi Pembelajaran Kimia (Journal of Innovation in Chemistry Education), 2024)
Green chemistry is one of the elective courses in the Chemistry Education Study Program of FKIP Untan, which focuses on methods to reduce or eliminate the use of chemicals. Learning media has an important role in the learning process as a learning resource to support the learning process. This study aims to determine the feasibility of E-Supplement Biomordan from Cengkodok Leaf (Melastoma malabathricum). The method used in this research is Research and Development (R&D) with the ADDIE development model. The data collection technique used was an indirect communication technique which was carried out by giving an assessment sheet in the form of a checklist to two experts. The assessment contains certain indicators that are assessed using a Likert scale assessment score. The results of the Green Chemistry e-supplement feasibility test obtained a result of 98% with a very feasible category so that it can be used in Green Chemistry courses.